(untitled) (Journal of the College of Basic Education, 2022)
Where the current research included the manufacture of models using the method of powders, where samples were prepared from taking nickel as a base material and alumina at a constant rate (10%), while titanium oxide (TiO2) was in percentages of (0,5,10,15,20)% and the powders were ground and mixed using a grinder. Homemade steel balls contained for one hour after which the samples were pressed at a pressure of 5 Ton for one minute. The prepared samples appeared at a temperature of 1300 °C and for a time only 2 hours. The SEM examination was performed as well as the physical examinations (hardness, radial compressive strength, wear), all before and after sintering. The results of the scanning electron microscope showed a clear microstructure and the best uniformity and crystal cohesion for it at the ratio 15% TiO2 As for the hardness only it gave the best hardness for Vickers at the ratio 15% TiO2 and reached 170.82Hv, while the diagonal compression resistance was the best value for it at the same The ratio also reached 49.5 MPa, while the wear values ​​decreased with increasing the concentration to reach the lowest when (20N) and at 15% TiO2.